Students' attitudes towards physical culture, physical education classes and exercises - Adrian Gądek (University of Applied Sciences in Tarnow, Poland, 2022)
Introduction: The notion of the attitude towards physical culture covers many terms with narrower meanings. A more precisely defined meaning includes all its various elements such as the attitude towards one's body, its physique, hygiene, fitness, various forms of rest and activity, etc. The aim of the research was to define the attitudes of youngsters graduating from secondary schools towards physical culture, physical education lessons and exercises. Material and methods: The research covered the senior year students from Tarnów who attended grammar schools, secondary technical schools and first degree vocational schools. The survey covered 751 students, 413 (55.0%) males and 338 (45.0%) females. The basic research method was a diagnostic survey. In order to obtain the necessary data which served to verify the hypotheses a survey technique was used with the following research tool: Questionnaire for testing the attitudes of young people towards physical culture S. Strzyżewski's. Results: As the research showed each index of students' attitudes towards physical culture was at the medium level, and the values ranged from 2.06 to 2.55 points. The average value of the global index of attitude amounted to 2.28 points. The highest result regarded the cognitive component (2.55), and the lowest average value was recorded in the case of the behavioural component (2.06). The greatest diversity of data was noticed in the behavioural component. Males obtained higher average values of the tested indices of attitudes than females. Conclusions: The obtained data show that the attitudes towards physical culture among the surveyed youngsters are shaped at a satisfying, although medium, level. The surveyed males obtained higher values both in individual components of the attitude and the global index. Secondary technical school students dominated over the other types of school.